2016
DOI: 10.1097/qai.0000000000000806
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Operational Research

Abstract: In resource-constrained settings, considerable delays in IPT initiation may occur, particularly in children with HIV who are presenting with cough at TB screening. The good safety profile of isoniazid in antiretroviral-therapy-experienced children provides further support to IPT implementation in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Among cohorts that did not receive LTBI tests, the cumulative TPT initiation and completion were similar if PLHIV were followed at HIV clinics or other clinics (S5 Fig [18,21,24,38,51,58,66,[70][71][72][73][74][75][76]78,79,82]. The most common facilitators were related to the initial steps (identification, initial LTBI testing, and completing LTBI testing) and to initiation and completion of TPT.…”
Section: Plos Medicinementioning
confidence: 96%
See 3 more Smart Citations
“…Among cohorts that did not receive LTBI tests, the cumulative TPT initiation and completion were similar if PLHIV were followed at HIV clinics or other clinics (S5 Fig [18,21,24,38,51,58,66,[70][71][72][73][74][75][76]78,79,82]. The most common facilitators were related to the initial steps (identification, initial LTBI testing, and completing LTBI testing) and to initiation and completion of TPT.…”
Section: Plos Medicinementioning
confidence: 96%
“…evaluated for TPT, and 40 (64%) of these cohorts were seen in HIV clinics. Twenty-one cohorts [17,[66][67][68][69][70][71][72][73][74][75][76][77][78][79] did not use LTBI tests, while 49 cohorts used LTBI tests; 22 used only TST, 12 used only IGRA, and 15 used either IGRA or TST. Among the 56 (80%) studies that reported the type of TPT regimen, mono-isoniazid regimens were the primary regimen prescribed in 50 cohorts (89%), and only one (2%) of the included cohorts primarily prescribed rifamycin-based short regimens (3 to months of rifampicin and isoniazid) [29].…”
Section: Plos Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…The level of awareness among health care providers, interruption of INH supply, co-infection with HIV, lack of recording tools for IPT and distance from health facilities affect uptake of the service in different settings. The IPT initiation and completion rates reported in research settings ranged between 18–33% and 23–50% respectively [ 7 – 10 ]. Whereas the IPT initiation and completion rates reported in program implementation settings were between 21–58% and 13% respectively [ 11 12 ].…”
Section: Introductionmentioning
confidence: 99%